2012
DOI: 10.1002/adfm.201201750
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Efficiency Fluorescent Single and Bi‐Layer Organic Light Emitting Diodes: The Key Role of Triplet Fusion

Abstract: A new family of anthracene core, highly fluorescent emitters is synthesized which include diphenylamine hole transport end groups. Using a very simple one or two layer organic light emitting diode (OLED) structure, devices without outcoupling achieve an external quantum efficiency of 6% and photonic efficiencies of 20 cd/A. The theoretical maximum efficiency of such devices should not exceed 3.55%. Detailed photophysical characterization shows that for these anthracene based emitters 2T1≤Tn and so in this spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
184
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 279 publications
(208 citation statements)
references
References 35 publications
7
184
0
2
Order By: Relevance
“…Maximum external quantum efficiencies (EQE) of about 6% or above have been obtained for DPA, perylene, and rubrene ( Figure 3c and Table S1, Supporting Information). These values exceed the EQE limit (5%) of conventional electrofluorescence (assuming an optical outcoupling factor of 0.2), [6][7][8] suggesting a significant contribution from triplets toward the total EL. We found that a high emitter doping concentration (20%) results in optimum OLED performance ( Figure S2, Supporting Information), consistent with the view that a small intermolecular separation is required for efficient bimolecular TTA process.…”
Section: Doi: 101002/adma201605987mentioning
confidence: 86%
See 3 more Smart Citations
“…Maximum external quantum efficiencies (EQE) of about 6% or above have been obtained for DPA, perylene, and rubrene ( Figure 3c and Table S1, Supporting Information). These values exceed the EQE limit (5%) of conventional electrofluorescence (assuming an optical outcoupling factor of 0.2), [6][7][8] suggesting a significant contribution from triplets toward the total EL. We found that a high emitter doping concentration (20%) results in optimum OLED performance ( Figure S2, Supporting Information), consistent with the view that a small intermolecular separation is required for efficient bimolecular TTA process.…”
Section: Doi: 101002/adma201605987mentioning
confidence: 86%
“…[5] Another strategy to utilize triplet excitons in fluorescent OLEDs is through the generation of singlets by triplet-triplet annihilation (TTA) or "triplet fusion." [6][7][8] At the same time, photon upconversion through TTA has been widely considered for next-generation photovoltaic applications. [9][10][11][12][13][14] Effective upconverters have been demonstrated using combinations of a triplet sensitizer such as platinum octaethylporphyrin (PtOEP) [3] and a triplet acceptor/annihilator such as 9,10-diphenylanthracene (DPA), [15] perylene, [16] or rubrene.…”
Section: Doi: 101002/adma201605987mentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable attention has been paid to white organic light-emitting devices (OLEDs) in flat panel displays (FPDs) and solid-state lighting in the next generation due to several potential advantages such as diffusive emission of surfaces, large-range area manufacturability, ecofriendliness, and effective fabrication process for the cost [1][2][3][4][5][6][7][8][9] . Such interesting advantages in white OLEDs have activated the field and, though they are entering the marketplace, outstanding challenges in achieving high efficiency and color rendering index (CRI) still remain.…”
mentioning
confidence: 99%